Режисура предметної дії: новий рівень партнерства на уроці - Мозговий, Віктор (My University, 2019)
Мета дослідження. Модернізація сучасної системи вітчизняної загальної середньої освіти та запровадження Концепції Нової української школи представили серйозні виклики вчителям. Поетапність реалізації Концепції та її результативність будуть залежати від того, наскільки сучасний учитель зможе вибудувати нову систему педагогічної взаємодії, у якій учень залишатиметься суб’єктом педагогічної, предметної, виховної взаємодії. Саме ці питання актуалізують сьогодні пошук нових підходів щодо режисури (вибудови) основної форми освітнього процесу – уроку. Методи дослідження. На основі теоретичного аналізу підходів щодо організації сучасного освітнього процесу акцентовано увагу на доцільності використання в сучасній дидактиці таких понять як навчання й учіння. Використовуючи метод класифікації, визначено та структуровано методи і прийоми навчання й учіння. Результат. Акцентовано увагу на доцільності використання режисури предметної дії як відповідного дидактичного рівня суб’єкт-субʼєктної взаємодії на уроці. Запропоновано припущення, що використання режисури предметної дії наблизить вчителя й учнів до формування нового освітнього середовища на засадах партнерської педагогіки. The purpouse of the study. The educational and upbringing problem of a free person has been actualized with the humanistic guidelines for the development of society. We should form the understanding of the definition “freedom” from the beginning of study. However, if you do not make appropriate the conditions for student, where he feels himself as the subject of the educational process, the ideas about education of free personality can be unfulfilled plans. Processes of modernization secondary education and the implementation of the Conception of New Ukrainian School are serious challenges for teachers. The effectiveness of innovations depends on teacher’s skills to build a new system of pedagogical interaction, where the student will be able to feel a full-fledged subject of pedagogical, substantive, educational action. The acceptance of the priority of such concepts as freedom, partnership, childhood, at the legislative level is very positive for educational system. Therefore, the questions about didactic and methodological rethinking and updating of the teacher's actions at the lesson are becoming so important. These questions require the search for new approaches to directing of subject action. Research methods. Realization of such research on the theoretical level requires the explanation of concept “directing of subject action”. It means the making of efficient cooperation between a teacher and a student as the partners. The position of partnership will provide the process of teaching and studying. Because of these aspects, we have paid attention to the efficiency of using such concepts as teaching and studying in modern didactic. We have determined and structured the methods and approaches teaching and studying. The meaning of these definition have been explained, classification has been represented according to realization of directing of subject action, based on partnership pedagogy. Result. We have paid attention to the efficiency of using the directing of subject action as appropriate didactic level of “subject to subject interaction” at the lesson. Hypothesis about the using of directing of subject action as a facilitator of the forming of new educational environment was made.
Keywords: режисура; directing; предметна дія; навчання; учіння; суб’єкт-субʼєктна взаємодія; партнерська педагогіка; бінарні методики; subject action; teaching; studying; subject to subject interaction; pedagogy of partnership; bilateral methods